“Strategies of Large Systems Integrators in Malaysia to Overcome Lower Margins” - Omardin, Daniel Yusoff (2013)
The Malaysian Information and Technology (IT) scene is now no longer seen as market for high returns as it has reached it peak. There has been a tremendous growth of IT related companies in the past 10 years. All this competition is now leading to a price war making the industry less attractive and harder for the system integrators that have been doing business in this market for the past 20 years. This paper investigates the lost of margins of three large system integrators in Malaysia and its strategy moving forward to overcome the low margins of less than 10%. The last time these companies saw margins of higher than 10% was last recorded in 2003. The researched investigates each company to understand the background of each company in regards to how the company came about, what was its strategy then, how has the company changed over the years and the strategy and core competency that it had to develop to stay relevant. The study then conducted an interview with the strategic decision maker of each organization to determine the current outlook and strategy moving forward.The information collected during the interview is then clarified and related back to Porter’s generic strategy and also Minztberg’s 5Ps and 10 schools of strategy. All three organizations “believe” they are embarking on a Differentiator Strategy (Porter, 1996) as describe in his paper in regards to generic strategy. However the sentiment of the employees and market feedback fails to connect with the organizations strategies as they are seen “embarking” on strategy as they go on with the day-to-day operations. As each organization has it’s own strategy the researcher questions the long-term sustainability of these strategies and provides recommendations along with future research possibilities.